2019
DOI: 10.1021/acsomega.9b00077
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of a New Class of Phosphorylated and Modified Flavonoids

Abstract: The surge of resistant food pathogens is a major threat worldwide. Previous research conducted on phytochemicals has shown their antibacterial activity against pathogenic bacteria. The design of antimicrobial agents to curb pathogenic disease remains a challenge demanding critical attention. Flavonoids such as apigenin and quercetin were evaluated against Gram-positive and Gram-negative bacteria. The results indicated that the antibacterial activity of each flavonoid occurred at a different minimum inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 42 publications
(129 reference statements)
3
56
2
Order By: Relevance
“…[48] also reported its efficacy against Shigella flexeneri NCIM5265 and Lactobacillus casei var Shirota. Strikingly, Osonga et al [49] documented that quercetin derivatives (e.g., quercetin 4 ,5-diphosphate (QDP), quercetin 3 ,4 ,3,5,7-pentaphosphate (QPP), quercetin 5 -sulfonic acid (QSA)) resulted in highly biocompatible, soluble, and potent antibacterial activity with 100% inhibition of Listeria monocytogenes, Pseudomonas aeruginosa, and Aeromonas hydrophila. Moreover, quercetin revealed the strongest antifungal activities against Candida albicans, Cryptococcus neoformans, and Aspergillus niger [50].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…[48] also reported its efficacy against Shigella flexeneri NCIM5265 and Lactobacillus casei var Shirota. Strikingly, Osonga et al [49] documented that quercetin derivatives (e.g., quercetin 4 ,5-diphosphate (QDP), quercetin 3 ,4 ,3,5,7-pentaphosphate (QPP), quercetin 5 -sulfonic acid (QSA)) resulted in highly biocompatible, soluble, and potent antibacterial activity with 100% inhibition of Listeria monocytogenes, Pseudomonas aeruginosa, and Aeromonas hydrophila. Moreover, quercetin revealed the strongest antifungal activities against Candida albicans, Cryptococcus neoformans, and Aspergillus niger [50].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…In addition, galangin exhibited selective anti-cytochrome and antifungal activity [25], and showed antimicrobial activity against S. aureus [25,32], and methicillin-sensitive and methicillin-resistant S. aureus, Enterococcus spp., and P. aeruginosa [33]. Flavone apigenin showed strong activity against Gram-negative bacteria [34], while quercetin and apigenin derivatives showed strong antibacterial properties against Gram-negative and Gram-positive bacteria [35]. Some phenolic acids (gallic, caffeic and ferulic acids) showed antibacterial activity against Gram-positive (S. aureus and Listeria monocytogenes) and Gram-negative bacteria (E. coli and P. aeruginosa) with a greater efficiency than conventional antibiotics such as gentamicin and streptomycin [36].…”
Section: Mic Assaymentioning
confidence: 99%
“…For example, it has been reported that glabrol, a flavonoid from licorice, displayed high efficiency against methicillin-resistant Staphylococcus aureus (MRSA) in both in vivo and in vitro models [6]. A new class of modified flavonoids namely apigenin and quercetin was found to completely inhibit the growth of Listeria monocytogenes, Pseudomonas aeruginosa, and Aeromonas hydrophila [7]. Some synthetic derivatives of flavonoids also displayed 20-to 80-fold more potent antimicrobial capacity than standard antibiotics against multidrug-resistant Gram-negative and Grampositive bacteria [8].…”
Section: Introductionmentioning
confidence: 99%